The Doctors Mayo - Clapesattle, Helen (New York Pocket Books, 1956)
Tells the story of the Mayo brothers and their contribution to the field of medicine.
Include Index
Keywords: Mayo, William Worrall, 1819-1911 -- Mayo, Charles H. (Charles Horace), 1865-1939 -- Mayo, William James, 1861-1939